MAKMODEL, A Macro-Econometric Model for the Republic of Macedonia - Leo de Haan; Aneta Naumovska; Marga Peeters (National Bank of the Republic of Macedonia, 2001)
This report describes the macro-econometric model for the Republic of Macedonia MAKMODEL. It documents the main features of this model that was built by research teams of the Macedonian and Dutch central bank during July 1999 - June 2001 as one module of a large scale PHARE-project, funded by the European Commission. Details on the statistical aspects of the Macedonian monthly data collected for the period 1993-1999 are provided, along with the construction and estimation of the econometric model. The last sections present some simulation and forecasting examples. The ultimate aim of MAKMODEL is to use it for macro-economic policy analyses at the Macedonian central bank, by means of keeping the statistical basis up to date, elaborating upon the model, and making forecasts and running simulations in the near future.
Keywords: C5; E17; 330; Macedonia; Econometric modelling; Forecasting and simulation